2019
DOI: 10.3390/ijerph16020245
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cardiorespiratory Exercise on Cognition in Older Women Exposed to Air Pollution

Abstract: The aim was to analyze the effects of cardiorespiratory exercise and air pollution on cognition and cardiovascular markers in four groups of older women: the active/clean air group (AC), the active/polluted air group (AP), the sedentary/clean air group (SC), and the sedentary/polluted air group (SP). Active groups performed a training task based on progressive walking. Prior to and after the experiment, the following parameters were assessed: cognition, by Mini Mental State Examination (MMSE); maximum oxygen u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 51 publications
2
9
0
Order By: Relevance
“…It has recently been reported that a multi-component physical exercise program did not improve cognitive function in participants with type 2 diabetes, perhaps because of the characteristics of the exercises program and the methodology design [63]. However, our results agree with several recent studies that reported improvements in cognitive deterioration in older women who carried out an aerobic exercise programme [64][65][66][67]. On the other hand, the CG showed a worse cognitive state after the 24-week study period, with a significant decrease in MMSE score (p < 0.001).…”
Section: Glycosylated Haemoglobinsupporting
confidence: 86%
“…It has recently been reported that a multi-component physical exercise program did not improve cognitive function in participants with type 2 diabetes, perhaps because of the characteristics of the exercises program and the methodology design [63]. However, our results agree with several recent studies that reported improvements in cognitive deterioration in older women who carried out an aerobic exercise programme [64][65][66][67]. On the other hand, the CG showed a worse cognitive state after the 24-week study period, with a significant decrease in MMSE score (p < 0.001).…”
Section: Glycosylated Haemoglobinsupporting
confidence: 86%
“…On the other hand, resistance training and clean air (AC group) showed the best results in muscular strength, with statistically significant differences with respect to the sedentary groups (SC and SP), and it also obtained better results than the AP group (who carried out the same training programme), especially in upper limb strength, where the differences were statistically significant (p < 0.5). These results are in line with those of studies which demonstrate that physical performance and adaptations to training stimuli are lower in environments of high air pollution [24,54], specifically in muscular strength, hence a recent study suggested that air pollution might be an important risk factor of poorer health and functional status as indicated by hand-grip strength [28].…”
Section: Muscular Strengthsupporting
confidence: 91%
“…Therefore, some evidence indicates that interventions to mitigate IGF-1 deficiency (i.e., exercise programmes) would improve cognitive state, however, it seems that further investigation is needed to know if this association exists between IGF-1 and cognitive impairment. It is known that aerobic exercise can be a protective factor against the effects of air pollution, increasing cognition and the mechanisms of oxygen transport [ 24 ]. In a similar way, muscular strength training could be an effective stimulation to improve cognitive function in older adults.…”
Section: Introductionmentioning
confidence: 99%
“…One short-term study explored the effects of exercise in different environments, while the results indicated that one 15-min bout of walking or jogging with or without air pollutants did not appear to affect participants' emotions (Han, 2020 ). There are also studies using aerobic and resistance training under the air pollutants conditions on cognition status (Molina-Sotomayor et al, 2019 , 2020 ), and their findings tended to show that exercise may be serve as a protective factor against the effects that pollution has on cognition. However, most of these studies use evaluation methods such as blood parameters or mental scales, and there is little research on the mechanism of cognitive function changes.…”
Section: Research Hotspots and Application Fields Analysismentioning
confidence: 99%